2008
DOI: 10.3181/0712-rm-352
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of Tumor Suppressor CEACAM1 with Beta Catenin: Identification of Key Residues in the Long Cytoplasmic Domain

Abstract: CEACAM1-4L (carcinoembryonic antigen cell adhesion molecule 1, with 4 extracellular Ig-like domains and a long, 71 amino acid cytoplasmic domain) is expressed in epithelial cells and activated T-cells, but is down-regulated in most epithelial cell cancers and T-cell leukemias. A highly conserved sequence within the cytoplasmic domain has ca 50% sequence homology with Tcf-3 and −4, transcription factors that bind β-catenin, and to a lesser extent (32% homology), with E-cadherin that also binds β-catenin. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 62 publications
(70 reference statements)
4
53
0
Order By: Relevance
“…How MiniSOX9, devoid of transactivation domain, can activate Wnt? It might be a consequence of SOX9 inhibition, because SOX9 upregulates ICAT (inhibitor of b-catenin and T-cell factor (TCF))/TCF interaction (Tago et al, 2000) and the Groucho-related corepressors TLE2-4 (Cavallo et al, 1998;Roose et al, 1998) in HT29Cl.16E cells (Bastide et al, 2007), as well as CEACAM1 , which binds to the armadillo repeats of b-catenin, thereby inducing its redistribution from the cytosol to the plasma membrane (Jin et al, 2008;Leung et al, 2008). Moreover, MiniSOX9 is able to activate the Wnt pathway on its own, through its capacity to bind to b-catenin and inducing b-catenin accumulation in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…How MiniSOX9, devoid of transactivation domain, can activate Wnt? It might be a consequence of SOX9 inhibition, because SOX9 upregulates ICAT (inhibitor of b-catenin and T-cell factor (TCF))/TCF interaction (Tago et al, 2000) and the Groucho-related corepressors TLE2-4 (Cavallo et al, 1998;Roose et al, 1998) in HT29Cl.16E cells (Bastide et al, 2007), as well as CEACAM1 , which binds to the armadillo repeats of b-catenin, thereby inducing its redistribution from the cytosol to the plasma membrane (Jin et al, 2008;Leung et al, 2008). Moreover, MiniSOX9 is able to activate the Wnt pathway on its own, through its capacity to bind to b-catenin and inducing b-catenin accumulation in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al (2008) have recently shown that CEACAM1-L directly associates with the b-catenin armadillo repeats. We have confirmed this finding and shown that CEACAM1-L binds to and colocalizes with b-catenin in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We thus examined expression and activity levels of key intestinal proteins in the Wnt signaling pathway as it usually sustains major alterations in intestinal cancer. In fact, Jin et al (2008) have recently shown by coimmunoprecipitation, glutathione-S-transferase (GST) pulldowns, mutational analyses, BiACore analyses and colocalization in breast cancer cells and human T lymphocytes that residues within the long cytoplasmic domain of human CEACAM1-L bind directly to the armadillo repeats of b-catenin. To verify expression or activity of key signaling proteins, cytosolic and nuclear fractions of total intestines were prepared ( Figure 3) and purity of these fractions was monitored by immunoblotting all intestinal samples with antibodies to HSP90 for cytosolic or laminB1 for nuclear fractions.…”
Section: Extra-intestinal Lesions Are Increased Inmentioning
confidence: 99%
“…the binding of SOX9 to DNA (Bastide et al, 2007). This inhibition might result from an upregulation of groucho-related inhibitors of the β-catenin-Tcf complex (Bastide et al, 2007) and of CEACAM1, a direct SOX9 target (Jin et al, 2008;Leung et al, 2008;Zalzali et al, 2008). Indeed, the W143R SOX9 mutant, which is unable to bind DNA, is unable to inhibit the Wnt-APC pathway, although it is able to repress PKCα expression, as shown in the present study.…”
Section: Sox9-dependent Pkcα Repression Involves Sp1mentioning
confidence: 54%